Reticuloendothelial system involvement in untreated sarcoidosis patients as assessed by 18F-FDG PET scanning. - Kalkanis, Alexandros; Judson, Marc A.; Kalkanis, Dimitrios; Vavougios, George D.; Malamitsi, Julia; Georgou, Evangelos (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Not available